Digital angiography: Moving with the times. (October 2017) - Costello, David; Kenny, Patrick; Lewis, Mandy
Abstract : Low dose Angiography (LDA) systems rely on significant recursive filtration (AKA temporal averaging) to maintain image quality. In situations of rapid motion, such processing can have a detrimental effect on images obtained, producing motion blur and temporal ghosting. LDA enables the use of lower kV's and mAs resulting in lower staff and patient doses. It also allows manufacturers to overcome output limitations when using smaller focal spots. While the benefits are clear very little work has been carried out in relation to the drawbacks of this approach. This work aims to examine the impact of recursive filtration on moving targets in LDA systems. Common test objects such as the Leeds Test Objects do not allow for the dynamic assessment of Image Quality. In this study, a NEMA Cardiology Phantom was modified to investigate the impact of Motion Unsharpness and Recursive Filtering on image quality in LDA. This investigation was carried out under conditions simulating normal clinical use. Systems assessed were: Philips Alura FD 20, Alura Clarity FD 10 and two Siemens Artis Zee systems. All systems using LDA demonstrated different levels of Temporal Ghosting. The Intensity and spacing of the ghost images was dependent on system type and pulse rate. When set to acquisition mode, the ghosting artefact was not present. However, an increase in motion unsharness as a result of longer pulse widths was observed. The impact of motion unsharpness and temporal ghosting impinges on the effective optimisation of clinical systems and should form of regular QC.